2015
DOI: 10.1124/jpet.115.228213
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Transporters at the Blood-Brain Barrier Limit Delivery and Efficacy of Cyclin-Dependent Kinase 4/6 Inhibitor Palbociclib (PD-0332991) in an Orthotopic Brain Tumor Model

Abstract: 6-Acetyl-8-cyclopentyl-5-methyl-2-([5-(piperazin-1-yl)pyridin-2-yl]amino)pyrido(2,3-d)pyrimidin-7(8H)-one [palbociclib (PD-0332991)] is a cyclin-dependent kinase 4/6 inhibitor approved for the treatment of metastatic breast cancer and is currently undergoing clinical trials for many solid tumors. Glioblastoma (GBM) is the most common primary brain tumor in adults and has limited treatment options. The cyclin-dependent kinase 4/6 pathway is commonly dysregulated in GBM and is a promising target in treating this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 35 publications
1
75
0
Order By: Relevance
“…Like many other anti-tumor agents, palbociclib is also subject to efflux by BBB transporters. Recent in vivo studies showed that both P-gp and BCRP restricted brain penetration of palbociclib, resulting in low drug levels (28,29). Therefore, we compared brain concentrations in mice of palbociclib when used alone vs. in combination with everolimus.…”
Section: Resultsmentioning
confidence: 99%
“…Like many other anti-tumor agents, palbociclib is also subject to efflux by BBB transporters. Recent in vivo studies showed that both P-gp and BCRP restricted brain penetration of palbociclib, resulting in low drug levels (28,29). Therefore, we compared brain concentrations in mice of palbociclib when used alone vs. in combination with everolimus.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting evidence is available. While Hashizume and colleagues reported sufficient levels of palbociclib in the brain, 11 the same group reported earlier results that demonstrated that palbociclib was a substrate for both P-glycoprotein and breast cancer resistance protein 10 and levels were 115-fold less than the transporter deficient mice when compared with wild-type mice. We did not measure the levels of palbociclib in the brain of orthotopic mice in our current study, however the amount of drug used (75 mg/kg/day) was sufficient to achieve an anti-proliferative effect and a significant extension in survival when combined with RT.…”
Section: Discussionmentioning
confidence: 97%
“…The concentration of many drugs is significantly lower at the infiltrating GBM rim as compared to the necrotic tumor core(28). This impaired drug delivery to infiltrating glioma may be associated with diminished efficacy of these drugs in orthotopic glioma models (32, 4143). TAL mirrors these experiences by demonstrating a lack of orthotopic efficacy despite activity in heterotopic models.…”
Section: Discussionmentioning
confidence: 99%